Pengaruh kepadatan kendaraan bermotor dan Produk Domestik Regional Bruto (PDRB) sektor transportasi terhadap pajak kendaraan bermotor Provinsi Sulawesi Utara tahun 2020-2024 - Pongilatan, Monica Gloria; Pangerapan, Sonny; Mintalangi, Syermi (Riset Akuntansi dan Portofolio Investasi, 2025)
Motor Vehicle Tax (PKB) is one of the main sources of local revenue for provinces in Indonesia, including North Sulawesi. This study aims to examine the effect of motor vehicle density and the Gross Regional Domestic Product (GRDP) of the transportation sector on Motor Vehicle Tax revenue in North Sulawesi Province during the 2020–2024 period. This research employs a quantitative approach using secondary panel data obtained from the Central Statistics Agency and the Regional Revenue Agency. Panel data regression analysis was conducted using the Fixed Effect Model with the aid of EViews 12. The results show that both motor vehicle density and transportation sector GRDP have a significant positive effect on Motor Vehicle Tax revenue. These findings suggest that increased mobility and economic activity in the transportation sector contribute significantly to regional tax revenue. This supports Musgrave’s theory regarding the role of economic growth in enhancing public revenue collection.